A Laser Dissection-RNAseq Analysis Highlights the Activation of Cytokinin Pathways by Nod Factors in the Medicago truncatula Root Epidermis . Issue 3 (23rd May 2016) - Jardinaud, Marie-Françoise; Boivin, Stéphane; Rodde, Nathalie; Catrice, Olivier; Kisiala, Anna; Lepage, Agnes; Moreau, Sandra; Roux, Brice; Cottret, Ludovic; Sallet, Erika; Brault, Mathias; Emery, R.J. Neil; et al.
Abstract : Nod factors induce massive reprogramming of gene expression in the root epidermis, including the CRE1 cytokinin pathway which leads to both positive and negative regulation of nodulation. Abstract: Nod factors (NF s) are lipochitooligosaccharidic signal molecules produced by rhizobia, which play a key role in the rhizobium-legume symbiotic interaction. In this study, we analyzed the gene expression reprogramming induced by purified NF (4 and 24 h of treatment) in the root epidermis of the model legume Medicago truncatula . Tissue-specific transcriptome analysis was achieved by laser-capture microdissection coupled to high-depth RNA sequencing. The expression of 17, 191 genes was detected in the epidermis, among which 1, 070 were found to be regulated by NF addition, including previously characterized NF -induced marker genes. Many genes exhibited strong levels of transcriptional activation, sometimes only transiently at 4 h, indicating highly dynamic regulation. Expression reprogramming affected a variety of cellular processes, including perception, signaling, regulation of gene expression, as well as cell wall, cytoskeleton, transport, metabolism, and defense, with numerous NF -induced genes never identified before. Strikingly, early epidermal activation of cytokinin (CK ) pathways was indicated, based on the induction of CK metabolic and signaling genes, including the CRE1 receptor essential to promote nodulation. These transcriptional activations were independently validated using promoter:β-glucuronidase fusions with the MtCRE1 CK receptor gene and a CK response reporter ( TWO COMPONENT SIGNALING SENSOR NEW ). A CK pretreatment reduced the NF induction of the EARLY NODULIN11 ( ENOD11 ) symbiotic marker, while a CK -degrading enzyme (CYTOKININ OXIDASE/DEHYDROGENASE3) ectopically expressed in the root epidermis led to increased NF induction of ENOD11 and nodulation. Therefore, CK may play both positive and negative roles in M. truncatula nodulation.